2011
DOI: 10.1186/1471-2180-11-211
|View full text |Cite|
|
Sign up to set email alerts
|

Membrane insertion and assembly of epitope-tagged gp9 at the tip of the M13 phage

Abstract: BackgroundFilamentous M13 phage extrude from infected Escherichia coli with a tip structure composed of gp7 and gp9. This tip structure is extended by the assembly of the filament composed of the major coat protein gp8. Finally, gp3 and gp6 terminate the phage structure at the proximal end. Up to now, gp3 has been the primary tool for phage display technology. However, gp7, gp8 and gp9 could also be used for phage display and these phage particles should bind to two different or more surfaces when the modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 18 publications
(26 reference statements)
2
17
0
Order By: Relevance
“…Here, the beneficial effects of pIX display was revealed only when pIX was utilized without the pelB signal sequence. Thus, the consequence of adding a pelB sequence could well be a re-routing from the YidC, the suggested route for native pIX13, to the SEC translocon. Moreover, the favorable properties appear to be unique to pIX, as M13 pVIII that also depends on YidC has been shown to be inferior to pIII in antibody affinity selection3637.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the beneficial effects of pIX display was revealed only when pIX was utilized without the pelB signal sequence. Thus, the consequence of adding a pelB sequence could well be a re-routing from the YidC, the suggested route for native pIX13, to the SEC translocon. Moreover, the favorable properties appear to be unique to pIX, as M13 pVIII that also depends on YidC has been shown to be inferior to pIII in antibody affinity selection3637.…”
Section: Discussionmentioning
confidence: 99%
“…pIX and pIII are located at opposite tips on the virion, and the two proteins differ in their mechanisms of translocation to the E. coli inner membrane prior to phage assembly. Whereas pIII is synthesized as a precursor with a post-translationally processed signal sequence and targets the SEC translocation pathway12, pIX altogether lacks a signal sequence, does not undergo post-translational processing and appears to depend on YidC for periplasmic targeting1213. Early studies showed that an N -terminal GST fusion prevented pIX display, as pIX was found aggregated in the cytosol of the E. coli host14.…”
mentioning
confidence: 99%
“…In line with this notion, it has been shown that pIX spontaneously adopts an a-helical structure when inserted into artificial lipid vesicles [28]. However, a very recent report exploiting a YidC-deficient host for virion production provides compelling evidence that at least the pIX capsid is also dependent on the YidC transporter for inner membrane targeting and subsequent virion integration [29].…”
Section: The Ff Biology and Phage Particle Architecturementioning
confidence: 91%
“…In one study, the 13 amino acid long AviTag was readily displayed on all copies of phage genome encoded pIX, (type 9 display, excluding wt complementation), but at the expense of markedly reduced virion production [103]. When a modified pIX harnessing affinity tags (T7-tag or HA) up to 36 amino acids supplied in trans from a plasmid and complementing an amber pIX M13 phage, this reduction in titer appeared lesser pronounced [29]. Notably, neither of these studies used an N-terminal signal sequence targeting of the pIX fusion, supporting our initial observation that efficient pIX display is not dependent on dedicated periplasmic targeting through a leader peptide.…”
Section: A New Signal Sequence Independent Display Approachmentioning
confidence: 96%
See 1 more Smart Citation